Hematopoietic Stem Cell Transplantation for DNA Double Strand Breakage Repair Disorders - Wolska-Kuśnierz, Beata; Gennery, Andrew R. (Frontiers in Pediatrics, 2020)
The ubiquitous presence of enzymes required for repair of DNA double strand breaks renders patients with defects in these pathways susceptible to immunodeficiency, an increased risk of infection, autoimmunity, bone marrow failure and malignancies, which are commonly associated with Epstein Barr virus (EBV) infection. Treatment of malignancies is particularly difficult, as the nature of the systemic defect means that patients are sensitive to chemotherapy and radiotherapy. Increasing numbers of patients with Nijmegen Breakage syndrome, Ligase 4 deficiency and Cernunnos-XLF deficiency have been successfully transplanted. Best results are obtained with the use of reduced intensity conditioning. Patients with ataxia-telangiectasia have particularly poor outcomes and the best treatment approach for these patients is still to be determined.